Four 3D Cd(II)-based metal organic hybrids with different N,N `-donor spacers: syntheses, characterizations, and selective gas adsorption properties - Bhattacharya, Biswajit; Dey, Rajdip; Pachfule, Pradip; Banerjee, Rahul; Ghoshal, Debajyoti (Crystal Growth & Design, 2013)
{Four new metal organic frameworks with bivalent cadmium, disodium succinate (Na(2)suc), and four different N,N'-donor ligands, i.e., {[Cd(L1)(suc)]center dot(H2O)(3)}(n) (1), {[Cd(L2)(suc)]center dot(H2O)(2)\

Flexible dicarboxylate based pillar-layer metal organic frameworks: differences in structure and porosity by tuning the pyridyl based N, N ` linkers - Dey, Rajdip; Bhattacharya, Biswajit; Pachfule, Pradip; Banerjee, Rahul; Ghoshal, Debajyoti (CrystEngComm, 2014)
{Dicarboxylate supported metal organic hybrids of Co(II), Zn(II) and Cd(II) have been synthesized using two different pyridyl based N, N' linkers having Schiff base functionalized site. The use of flexible dicarboxylate glutarate in designing such frameworks has created a marked diversity in topology. The different N, N' donor linkers also played an active part in the channel modification in the synthesized MOFs. The structural and topological diversity has been analyzed from the single crystal X-ray structure. Five compounds, {[Co(azpy)(glut)]center dot(CH3OH)}(n) (1), {[Co(meazpy)(glut)(H2O)(2)]center dot (H2O)(3)

Syntheses, X-ray structures, catalytic activity and magnetic properties of two new coordination polymers of Co(II) and Ni(II) based on benzenedicarboxylate and linear N,N `-donor Schiff base linkers - Bhattacharya, Biswajit; Maity, Dilip Kumar; Pachfule, Pradip; Colacio, Enrique; Ghoshal, Debajyoti (Inorganic Chemistry Frontiers, 2014)
{Two isostructural coordination polymers based on Co(II) and Ni(II), {[M(azpy)(3)(p-bdc)(2)(H2O)(4)]center dot(CH3OH)(2)(H2O)(3)}(n) [where M = Co (1) and Ni (2); azpy = N,N'-bis-pyridin-4-ylmethylene-hydrazine and p-bdc = 1,4-benzenedicarboxylate], have been synthesized using mixed ligand systems at room temperature and characterized by single-crystal X-ray diffraction and other physicochemical methods. Structure determination reveals that both the complexes crystallize in the monoclinic space group C2/c and exhibit one-dimensional (1D) ladder like structures constructed by p-bdc and azpy ligands in which Schiff base (azpy) linkers serve as a bridging as well as pendent ligands. These pendent ligands are involved in H-bonding and pi-pi interactions with lattice water, methanol molecules and bridging azpy ligands, to form the 3D supramolecular structure. Notably, both the frameworks efficiently catalyze the Knoevenagel condensation reactions of a wide range of substituted benzaldehydes with active methylene compounds in heterogeneous medium under environmentally friendly conditions and the products were obtained in excellent yields. These catalysts were also found to exhibit excellent recyclability and re-usability without any significant loss of activity. A variable temperature magnetic study of both compounds was carried out and their magnetic properties justified on the basis of their crystal structure.

Different mechanical responses of dimorphic forms of anthracene schiffbase crystal - Lakshmipathi, Madhumathi; Tothadi, Srinu; Emmerling, Franziska; Bhattacharya, Biswajit; Ghosh, Soumyajit (Journal of Molecular Structure, 2022)
We obtained concomitant dimorphic forms of Anthracene Schiffbase (N-(anthracen-9-yl methylene)-2,5dichloroaniline) from hexane solvent. Two polymorphs can be differentiated by their morphology and mechanical properties. One form is long acicular type and elastically bendable while another form is block shaped and brittle in nature. Mechanical property is attributed to underlying crystal packing. Hirshfeld analysis and energy framework calculations were done to corroborate structure-property correlation of two forms (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Anthracene schiffbase; Dimorphs; Elasticity; mechanical properties

Simultaneously mechanically flexible, photobending, and acidochromic cyanostilbene molecular crystals - Parthasarathy, Thiyagaraj; Mishra, Manish Kumar; Bhattacharya, Biswajit; Emmerling, Franziska; Ghosh, Soumyajit (Crystal Growth & Design, 2024)
Molecular crystals that respond to multiple stimuli are gaining significant attention for their potential in smart materials like actuators and sensors. However, imparting multiple stimuli-responsive properties to a single crystal remains a major challenge. Herein, we report two cyanostilbene derivative-based crystals 1 and 2, with various responses to stimuli such as mechanical stress, light, acid vapors, etc. Both crystals 1 and 2 demonstrated mechanical flexibility and reversible acidochromism. Additionally, crystal 1 also exhibited light-induced photobending, which is ascribed to Z to E photoisomerization. Detailed structure-property correlation was established to unravel distinct mechanical responses. The development of these multitasking crystals may find applications in multitasking actuators, anticounterfeiting materials, and more.

Reversible twisting-induced crystalline-polycrystalline transformation in cyanoacrylate crystals - Parthasarathy, Thiyagaraj; Bhowmik, Aritra; Bhattacharya, Biswajit; Mishra, Manish Kumar; Ghosh, Soumyajit (Chemical Communications, 2026)
We report cyanoacrylate-based organic crystalline materials that exhibit reversible hand-induced helical twisting through the combined action of 1D elasticity and 2D plasticity. These crystals twist and untwist without lattice damage, retaining their elastic integrity through pi slip-stacking and Cl & ctdot;Cl, C-H & ctdot;Cl, and Me & ctdot;Me interactions. Their unique integration of elastic recovery, plastic bending, and reversible twisting highlights their potential as mechanically adaptive materials for flexible and responsive devices.